High-intensity warm-up, inhibition of glycolysis, and its practical consequences - Müller, A.; Tschakert, G.; Moser, O.; Gröschl, W.; Hofmann, P. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
It was hypothesized that submaximal but anaerobic work for 5 min can be maintained even if blood lactate concentration is elevated substantially by means of arm crank exercise although net-lactate increase is diminished but can be compensated by an increased oxygen uptake.